2020
DOI: 10.3389/fneur.2020.592825
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype, Sleep, and Depressive Symptoms Among Chinese College Students: A Cross-Sectional Study

Abstract: Objective: To describe the prevalence of chronotype and depressive symptoms among Chinese college students and to examine the association between chronotype and depressive symptoms.Methods: From April to May 2019, a cross-sectional survey was conducted among 1,179 Chinese college students from 2 universities in Anhui and Jiangxi provinces. A total of 1,135 valid questionnaires were collected, the valid response rate was 98.6%. The questionnaire investigated age, gender, major, height, weight, only child status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 49 publications
5
15
1
1
Order By: Relevance
“…Therefore, the healthier group, M-types were recognized as the control group. 30 , 31 All statistical tests were two-sided and significance was set at p <0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the healthier group, M-types were recognized as the control group. 30 , 31 All statistical tests were two-sided and significance was set at p <0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the healthier group, M-types were recognized as the control group. 30,31 All statistical tests were two-sided and significance was set at p<0.05. The interaction effects of sleep duration and chronotype on inflammatory cytokines are shown in Table 2.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…M-types have been suggested to be more conscientious, agreeable, and achievement-oriented. In contrast, E-types have been indicated to be slightly more extroverted, exhibit neurotic traits, and are more disposed to mental or psychiatric, mood, personality disturbances, and eating disorders [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…[21] On the other hand, a study of 1,179 Chinese university students found an association of moderate to severe depressive symptoms with poor quality sleep in the three chronotypes analyzed. [22] This suggests that sleep disorders are not only an outcome of depressive symptoms but may also predict such symptoms, a fact confirmed in studies with young adults. [21,22] The researchers explain that college students often give up sleep time and leisure activities to attend academic tasks (work or conducting internet research) and make nighttime use of the computer and other electronic media.…”
Section: Discussionmentioning
confidence: 81%
“…[22] This suggests that sleep disorders are not only an outcome of depressive symptoms but may also predict such symptoms, a fact confirmed in studies with young adults. [21,22] The researchers explain that college students often give up sleep time and leisure activities to attend academic tasks (work or conducting internet research) and make nighttime use of the computer and other electronic media. This makes sleep times irregular and sleep time insufficient, which reduces sleep quality, which increases the chance of depressive symptoms in this population.…”
Section: Discussionmentioning
confidence: 81%